(untitled) (Journal of Parents and Teachers, 2026)
To mark the International Day of Non-Violence and Peace, a selection of texts has been compiled that address this aspiration shared by so many people: peace. Religious leaders and philosophers have repeatedly called for a world without war, yet war continues to exist. The texts by Fray Luis de León, José Cadalso, Miguel Hernández, Aldous Huxley, Antonio Machado, Ramón María del Valle Inclán, amongst others, presented here can serve as a basis for reflection and discussion in the classroom, under the guidance of the teacher.